Between reform and revolution : German socialism and communism from 1840 to 1990 - Barclay, David E., 1948-; Weitz, Eric D. (Berghahn Books, 1998)
"The powerful impact of Socialism and Communism on modern German history is the theme which is explored by the contributors to this volume. Whereas previous investigations have tended to focus on political, intellectual and biographical aspects, this book captures, for the first time, the methodological and thematic diversity and richness of current work on the history of the German working class and the political movements that emerged from it. Based on original contributions from U.S., British, and German scholars, this collection address a wide range of themes and problems."--